ANALISIS DAN PERANCANGAN DESIGN UI/UX PADA WEB INFO LOKER KARAWANG METODE USER CENTERED DESIGN (UCD) - Satjadipoera, Raden Emir Alfarisy; Kurniwati, Ika (Scientica: Jurnal Ilmiah Sains dan Teknologi, 2024)
Websites are the main source of information for job seekers, especially in industrial cities like Karawang. However, job vacancy sites often face navigation problems and low user engagement. This research aims to improve the quality of the Karawang job vacancy information site using a User Centered Design (UCD) approach. UCD involves users in the design process to meet their needs. This research consisted of four stages: data collection through surveys, interviews, and observations; data analysis; wireframe and prototype design; as well as evaluation through usability testing. The results show improvements in ease of navigation, speed of access, and suitability of features to user needs. In conclusion, UCD is effective in improving site performance and user experience. Suggestions for further development include adding features, improving visual design, and optimizing for mobile devices, so that the Karawang job vacancy info site can continue to provide added value for users.